Of Bodies and Symptoms. Anthropological Perspectives on their Social and Medical Treatment - Sylvie Fainzang (ed.) (Antropologia Mèdica, 2011)
The question of the social treatment of the body and its transformations emerges in relation to issues of varying types (economic, therapeutic, ideological, cultural, aesthetic commercial, technical). This book examines the various ways of managing bodily symptoms or transformations and the social stakes and systems of knowledge which relate to them, both on the medical and social level. The contributions provide analyses that concern a broad range of countries. Through the themes it tackles and the subjects it examines, this book reveals both the universal nature of the questions it asks, and the evolution of the objects and approaches of anthropology itself.